Sejarah dan Perkembangan Pendidikan Islam di Malaysia - Mohd Roslan Mohd Nor (At-Ta'dib, 2011)
The aim and purpose of education in Islam is among others to form acohesive Muslim personal in the development of spiritual, physical, emotional,intellectual and social. It is not only produced good citizens but also covers theformation of a complete human capital in terms of religious and worldly life.In addition, the education that is based on the teachings of Islam also aimed atproducing righteous human that can meet the needs of the world and life inthe hereafter. The main focus of this article is about the history and developmentof Islamic Education subject in Malaysia. It also includes the etymology ofeducation and the Islamic education debate from the views of scholars andacademics. Discussions also focused on the development of Islamic educationsubject in Malaysia in the early period of Islam, development during the Westerncolonization and development of education in Islam after the country gainedindependence.